Variabilidade termo-higrométrica entre áreas de banhado, lavoura e fragmento florestal em situação de inverno e verão em Ernestina, RS - Borges, Denise Cristina (2017)
This dissertation is centered on the thermo-hygrometric analysis of an area of the city of Ernestina, located on the proximities of the Ernestina’s reservoir, on the hydrographic basin of Alto Jacuí. The microclimatic approach is used to analyze how de differences on the usage of the land can influence on the variation of air temperature and relative humidity. The area selected for the study presents three different kinds of use of the land: soy plantation, swamps and forest fragments. The study was conducted during two seasons: summer and winter, with in loco observations and measurements of the thermal conditions through the installation of mini weather shelters in each pf the three lands, identified in the research area. A qualitative survey was made for a better description of the areas and, from the collected data of the temperature and humidity, a qualitatity-quantitative analysis, a significance test and a temporo-spatial panel were made, through descriptive statistics method. It was concluded that the part with forest fragment presented a smaller oscillation of temperature and humidity, with lower indices on both stations compared with the other areas. On the tilth area, the moments of exposition and mulching interfered, causing a higher variability and thermal differences on day/night cycles in each of the seasons. On the swamp area, because of the periods of flood and drought, there was a higher thermal variability and different variations on seasons. This research contributes to the comprehension of the variation of climatic attributes associated to the different uses of the land influenced by the vegetation, and enhances the relevance of conducting further investigations in microclimatic scale with analytical potential, indicating reflections to new studies of natural areas and in different environments from the urban conformation.